An Etymological Study of Some Selected Names of Anatomy Science - Golnar Ghalekhani (Journal of Research on History of Medicine, 2018)
Anatomy is one of the most fundamental sciences related to medical science. Specialized vocabularies related to this science is often made by using the vocabularies available in Greek and Latin languages. Interestingly, many of these vocabularies have the same roots with the vocabularies in Persian language. The current Persian language is a continuation of the Middle Persian language, which is the continuation of Old Persian language itself, and the Old Persian along with the other Iranian Languages and ancient languages of India and the ancient European languages, all of which are rooted in the more ancient language called Indo-European languages. In the present research, seventeen fundamental words and their roots have been investigated, which we can see their association with the Persian language. The words used in this Research include the root of the names of body members such as the head, brain, eye, mouth, etc.; as the vocabularies used for composing specialized vocabularies, which will be considered here.